ISSUES OF SCIENTIFIC HUMAN PERFECTION IN THE WORKS OF ALISHER NAVAI - Uzoqjonova Moxinur Diyorbek qizi (Лучшие интеллектуальные исследования, 2024)
Annotation. This article expresses Alisher Navoi's ideas about the creation of images of a perfect person, education and upbringing in his artistic works, as well as the content, ways and methods of forming a perfect person in his educational and moral works.